2014
DOI: 10.1016/j.geomorph.2013.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Micromechanics of quartz sand breakage in a fractal context

Abstract: 19From a Quaternary science perspective, sand-sized quartz as well as silt-sized quartz is often 20 acknowledged as final products of glacial abrasion through different evolution mechanisms. This view 21 challenges the existence of any universal comminution process, which may relate the formation of detrital 22 quartz sand and silt. The contribution of grain size, energy input, and crystalline integrity in the scale of 23 quartz crushability has long been matter of much debate. The present empirical work exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…Recent empirical studies (Langroudi et al, 2014) have revealed that quartz grain fracturing is not necessarily the result of energy input, nor a function of duration and grain size at the start of the process, but is more controlled by internal defects in quartz. However, it has been suggested that quartz grains with characteristic outlines reflecting their origin become fragmented due to cryogenic cracking, as a result of a combination of thermal shock, ice crystal growths in fissures, and hydration shattering (Schwamborn et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Recent empirical studies (Langroudi et al, 2014) have revealed that quartz grain fracturing is not necessarily the result of energy input, nor a function of duration and grain size at the start of the process, but is more controlled by internal defects in quartz. However, it has been suggested that quartz grains with characteristic outlines reflecting their origin become fragmented due to cryogenic cracking, as a result of a combination of thermal shock, ice crystal growths in fissures, and hydration shattering (Schwamborn et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…If sediment is comminuted within till, then a complex history of grain loading and unloading (e.g. Rose and Hart, 2008; Langroudi and others, 2014) in a persistently wet environment might promote subcritical crack growth (e.g. Atkinson, 1984) that is not facilitated by EPD.…”
Section: Discussionmentioning
confidence: 99%
“…Observations from other workers indicate that there is no clear boundary between crushing and abrasion processes (e.g. Rogers et al, 1963; Chaolu, 1997; Langroudi and others, 2014). The observation of rounded sand-sized quartz grains (e.g.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…In general, the breakage potential of a soil particle increases with its size [22]. Using a large-sized ring shear apparatus, particle breakage can be measured by the grain size distribution curve before and after shearing [23,24]. However, the mechanical behavior due to particle breakage in different drained and shear velocity conditions is not fully understood.…”
Section: Introductionmentioning
confidence: 99%